PEDAGOGICAL CONDITIONS FOR IMPLEMENTING THE ESGBASED METHODOLOGICAL SYSTEM INTO THE EDUCATIONAL PROCESS (World Bulletin of Management and Law, 2026)
This article analyzes the pedagogical conditions for introducing a methodological system based on the principles of ESG (Environmental, Social, Governance) into the higher education process on a scientific basis. The study examines the structural structure of ESG-competence, the theoretical and methodological foundations of its formation, integrated educational technologies and a pedagogical monitoring system. Using content analysis, expert assessment, pedagogical experiment and mathematical statistics, the effectiveness indicators of the methodological system based on ESG were determined. The results of the study show that it is necessary to satisfy three main pedagogical conditions when implementing this system: organizationaldidactic, motivational-axiological and monitoring-based management conditions